2008
DOI: 10.1073/pnas.0707854105
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells possess distinct secretory granule subsets whose exocytosis is regulated by different SNARE isoforms

Abstract: Mast cells degranulate and release the contents of intracellular secretory granules in response to the cross-linking of FcRI by multivalent antigens. These granules contain a variety of biologically active inflammatory mediators; however, it is not clear whether these granules are homogenous or whether there is heterogeneity within the secretory granule population in mast cells. By using genetically altered mice lacking specific vesicleassociated SNARE membrane fusion proteins, we found that VAMP-8-deficient m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
189
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(205 citation statements)
references
References 20 publications
(34 reference statements)
13
189
0
1
Order By: Relevance
“…We first confirmed the role of VAMP8 in secretion by showing that knockdown of VAMP8 reduced secretion, similar to previous mast cell studies (Lippert et al , 2007; Puri & Roche, 2008; Tiwari et al , 2008), and that this effect could be rescued with wild‐type VAMP8 (Figs 4A and EV5D and E). Of note, the sequence homolog VAMP3, VAMP4, and VAMP7 did not rescue the secretion defect in cells with siRNA knockdown of endogenous VAMP8 (Fig EV5F).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…We first confirmed the role of VAMP8 in secretion by showing that knockdown of VAMP8 reduced secretion, similar to previous mast cell studies (Lippert et al , 2007; Puri & Roche, 2008; Tiwari et al , 2008), and that this effect could be rescued with wild‐type VAMP8 (Figs 4A and EV5D and E). Of note, the sequence homolog VAMP3, VAMP4, and VAMP7 did not rescue the secretion defect in cells with siRNA knockdown of endogenous VAMP8 (Fig EV5F).…”
Section: Resultssupporting
confidence: 89%
“…Markedly, this pruned list contained 2 phosphopeptides from a 100 amino acid long SNARE protein (Figs 1F and EV2C), vesicular‐associated membrane protein 8 (VAMP8), that is known to be critical for the fusion of vesicles with the plasma membrane during mast cell secretion (Lippert et al , 2007; Puri & Roche, 2008; Tiwari et al , 2008) but was not previously known to be regulated by phosphorylation. Using antibody staining, we confirmed that VAMP8 localizes to secretory granules before stimulation and translocates to the plasma membrane after antigen stimulation (Fig 1G).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, caspase-3 appears to be present in secretory vesicles distinct from those that are released by IgE-mediated mechanisms. Clearly, this may be in line with recent studies that have identified granule subtypes of distinct contents in mast cells (31).…”
Section: Discussionsupporting
confidence: 77%
“…The exact localization of STX11 in mast cells is still unclear. It has been recognized that mast cells have different secretory granule subsets characterized by different SNARE proteins able to selectively lead their release [30]. Interestingly, neutrophils, a cell type with a dominant exocytosis activity and heterogeneous granules, show a diminished degranulation capacity in absence of STX11.…”
Section: Discussionmentioning
confidence: 99%